Cómo la pragmática apoya el desarrollo de la competencia intercultural luchando contra los estereotipos nacionales y el humor de denigración - Tatoj, Cecylia (Studia Romanica Posnaniensia, 2023)
For some time now, great importance has been attached to intercultural competences in teaching foreign languages. The aim of this article is to present the contribution of cognitive grammar and pragmatics to this thematic axis in Spanish as a foreign language class. To achieve this, we will focus on the concept of prototype and stereotype. For this we will proceed to deciphering the meanings contained in the word „Spaniard”. Next, we will try to explain the reasons for their occurrence by observing some communicative behaviors that can also form the basis of denigration humor. We believe that linguistics can help in teaching intercultural competences as it helps to understand the causes of various misunderstandings that arise between representatives of different nations; misunderstandings, which often become the basis of various stereotypes reflected in slanderous humor. It is worth adding that the role of linguistics in this area is not only to convey knowledge about a specific language – in this case Spanish – but also to help understand the functioning of the human language and in this way educate future generations. Only by understanding the processes taking place in stereotypes, i.e., how they arise, how they work and how they can be reflected in humor, will we be able to overcome them.